2016
DOI: 10.17058/reci.v6i2.6370
|View full text |Cite
|
Sign up to set email alerts
|

Bias in case - Control studies: Can it be avoided?

Abstract: Exceto onde especificado diferentemente, a matéria publicada neste periódico é licenciada sob forma de uma licença Creative Commons -Atribuição 4. Justificativa e Objetivos: Embora os estudos de caso-controle tenham inúmeras vantagens, eles são vulneráveis a vieses que podem mascarar os verdadeiros resultados do estudo e, portanto, devem ser interpretados com cautela. O objetivo deste artigo é realizar criticamente esta abordagem, através de uma revisão da literatura, os erros que podem afetar este tipo de des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…First, despite the fact that all the included studies were adjusted for a variety of variables, other confounding factors may have had an impact on the results, factors such as lifestyle and genetic factors, which could not be accommodated in the current meta‐analysis. Second, due to fact that this study was based on observational studies, a causal link could not be drawn (Sedgwick, 2015; Souza et al, 2016). Third, as depressive symptoms as an outcome in this study were reported as a binary indicator, the risk estimate could only be an approximation of the underlying effects of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…First, despite the fact that all the included studies were adjusted for a variety of variables, other confounding factors may have had an impact on the results, factors such as lifestyle and genetic factors, which could not be accommodated in the current meta‐analysis. Second, due to fact that this study was based on observational studies, a causal link could not be drawn (Sedgwick, 2015; Souza et al, 2016). Third, as depressive symptoms as an outcome in this study were reported as a binary indicator, the risk estimate could only be an approximation of the underlying effects of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Cases were eligible if they were; (A) aged 18–50 years, (B) had clinical diagnosis of schizophrenia, (C) no co‐morbidity of mental disorders, chronic medical illness, or mental retardation. Since controls should have an exposure distribution identical to the population that is a source of cases (de Oliveira Souza et al, 2016) controls were selected from relatives, friends, and caregivers of people with schizophrenia when they visit the target hospital during the study period. Controls were eligible if they were; (A) aged from 18 to 50 years, (B) if they were relatives, friends and or caregivers of “cases,” (C) no history of chronic medical/psychiatric illnesses or mental retardation.…”
Section: Methodsmentioning
confidence: 99%